A T-duality of non-supersymmetric heterotic strings and an implication for Topological Modular Forms - Vivek Saxena (Journal of High Energy Physics)
Abstract Motivated by recent developments connecting non-supersymmetric heterotic string theory to the theory of Topological Modular Forms (TMF), we show that the worldsheet theory with central charge (17, 3 2 $$ \frac{3}{2} $$ ) obtained by fibering the (E 8)1 × (E 8)1 current algebra over the two N $$ \mathcal{N} $$ = (0, 1) sigma model on S 1 with antiperiodic spin structure (such that the E 8 factors are exchanged as we go around the circle), is continuously connected to the (E 8)2 theory in the Gaiotto Johnson-Freyd Witten sense of going “up and down the RG trajectories”. Combined with the work of Tachikawa and Yamashita, this furnishes a physical derivation of the fact that the (E 8)2 theory corresponds to the unique nontrivial torsion element [(E 8)2] of TMF31 with zero mod-2 elliptic genus.